Utilization of Uses and Gratifications in Media Use Literature During the Covid-19 Pandemic - Liestia, Maria Natasha (Journal of Social Research, 2023)
This research delves into the application of Uses and Gratifications (UGT) theory within the literature analyzing media consumption during the Covid-19 pandemic. Its primary objective is to elucidate and evaluate the usage of UGT in this context, supported by empirical findings and relevant theoretical frameworks. Employing a systematic literature review methodology, the study conducted a literature search in December 2021, utilizing the keywords "Uses and Gratifications" and "Covid." Through a meticulous process of inclusion and extraction, the researchers identified and analyzed 31 studies out of 214 journal articles that aligned with the search criteria. The amassed findings showcased that UGT wielded substantial influence over media users and their media consumption patterns during the pandemic. Moreover, the research unveiled the untapped potential of UGT as a fundamental theory that could further enrich the scope of investigations into media usage during crises. However, to enhance its application, the study advocates for variable adjustments, such as increasing the number of samples studied, to foster more comprehensive and robust future research. This systematic literature review emphasizes the significance of UGT in understanding media behaviors during the Covid-19 pandemic. It offers valuable insights to scholars and researchers, encouraging them to build upon these discoveries, thereby advancing our comprehension of media utilization trends amidst times of adversity. By leveraging UGT as a theoretical foundation, scholars can delve deeper into the intricacies of media consumption and its effects on individuals and society during periods of significant disruption and uncertainty.